Raging Waters : China, India, Bangladesh, and Brahmaputra River Politics - Samaranayake, Nilanthi; Wuthnow, Joel; Limaye, Satu P. (Book collections on Project MUSE., 2018)
"Water scarcity is a difficult but important subject to address. Lectures on the topic usually begin with a complex diagram mapping the large number of issue areas that illustrates how vitally important water is to every facet of human existence. However, another message becomes apparent to students: water scarcity is an expansive topic and therefore theoretically problematic. From the start complications arise due to the pervasive nature of water. Water underwrites human life, so how can we begin to discuss it in isolation from other variables? Does water scarcity cause conflict or does conflict cause water scarcity? Is water scarcity due to a lack of availability or to ineffective allocation? Are the problems solved by building more infrastructure or does the spread of infrastructure lead to more water exploitation? Unfortunately, the best answer to most of these questions is: "it depends." Water scarcity is subject to a wide variation of conditions, depending on the uniqueness of each geographical area. Case studies, such as those used in Raging Waters: China, India, Bangladesh, and Brahmaputra River Politics are vitally important to understanding the broader impacts across a basin, but the ubiquitous nature of water confounds research efforts."--Provided by publisher.